THE IMPACT OF INTELLECTUAL CAPITAL DISCLOSURE ON COST OF EQUITY CAPITAL IN FINANCIAL REPORT OF BANKING SECTOR COMPANIES REGISTERED ON THE INDONESIA STOCK EXCHANGE - Sirait B1034161001, Evita Desmiyati (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
ABSTRACTObjective of this study is to determine the impact of intellectual capital disclosure on cost of equity capital in financial reporting of banking sector companies registered on the Indonesia Stock Exchange. This study used intellectual capital disclosure as independent variable, cost of equity capital as dependent variable, and firm size as moderation variable. This method used is quantitative approach. Data of research is secondary data, using annual report of companies listed in the Indonesia Stock Exchange gained through www.idx.co.id. Samples research were selected by using purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. The result of this study indicate that intellectual capital disclosure has negative significant effect on cost of equity capital, human capital disclosure has negative significant effect on cost of equity capital, structural capital disclosure has no significant effect on cost of equity capital, relational capital has positive significant effect on cost of equity capital, and firm size as a moderating variable has no individual effect but it can be as predictor variable on the relationship of intellectual capital disclosure to the cost of equity capital.Keywords: intellectual capital disclosure, cost of equity capital, size firmÂ REFERENCES(n.d.). Retrieved from Bursa Efek Indonesia (IDX): www.idx.co.idAbeysekera, I. (2011). The relation of intellectual capital disclosure strategies and market value in two political settings. Journal of Intellectual Capital, Vol. 12 No. 2 pp. 319-338.Aisyah, C. N., & Sudarno, S. (2014). Penagruh Struktur Kepemilikan dan R&D Terhadap Luas Pengungkapan Modal Intelektual. Dipenogoro Journal of Accounting, Vol 3 No 1, pp. 1-9.Arjuwati, B. (2016). Pengaruh Kinerja Intellectual Capital Terhadap Intellectual Capital DIsclosure pada Perusahaan yang Listing di Bursa Efek Indonesia. Padang: Kementrian Riset, Teknologi dan Pendidikan Tinggi Politeknik Negeri Padang.Bontis, N., & Kristandi, G. (2007). The Impact of Voluntary Disclosure on Cost of Equity Capital Estimates in a Temporal Settings. Journal of Intellectual Capital, 8 (4) pp. 577-594.Bontis, N., Keow, W., & Richardson, S. (2000). Intellectual Capital and Business Performance in Malaysian Industries. Journal of Intellectual Capital, 1 (1), pp. 85-100.Boujelbene, A. M., & Affes, H. (2013). The Impact of Intellectual Capital Disclosure on Cost of Equity Capital: A Case of French Firms. Journal of Economics, Finance and Administrative Science.Cahyati, A. (2012). Intellectual Capital: Pengukuran, Pengelolaan dan Pelaporan. Jurnal Riset Akuntansi & Komputerisasi Akuntansi, 3 (1).Chen, M., Cheng, S., & Hwang, Y. (2005). An Empirical Investigation of the Relationship Between Intellectual Capital and Firm's Market Value and Financial Performance. Journal of Intellectual Capital, 6 (2), 159-176.Chu, S. K., Chan, K. H., & Wu, W. W. (2011). Charting Intellectual Capital Performance of the Gateway to China. Journal of Intellectual Capital, 12 (2), pp. 249-276.Edvinsson, L., & Malone, M. (1997). Intellectual Capital: Realizaing your Company's True Value by Finding Its Hidden Brainpower. New York: Harper Business.Efferin, S., Darmadji, S. H., & Tan, Y. (2018). Metode Penelitian Akuntansi Mengungkap Fenomena dengan Pendekatan Kuantitatif dan Kualitatif. Graha Ilmu.Espinosa, M., & Trombetta, M. (2007). Disclose interactions and the cost of equity capital: Evidence from the Spanis Continuous Market. Journal of Business Finance and Accounting, 34(9-10), 1371-1392.Evans, T. G. (2003). Accounting Theory: Contemporary Accounting Issues. South-Western,Thomson,Australia.Francis, J. R., Khurana, L. K., & Pereira, R. (2005). Disclosure Incentives and Effects on Cost of Capital Around The World. Accounting Review, 80 (4): 1125-1162.Francis, J., LaFond, R., Olsson, P., & Schipper, K. (2005). The market pricing of accruals quality. Journal of Accounting & Economics, 295-327.Freedman, M., & Jaggi, B. (2005). Global Warming, Commitment to The Kyoto Protocol and Accounting Disclosures by The Largest Global Public Firms from Polluting Industries. The International Journal of Accounting, 40, pp. 215-232.Freeman, R., & Reed. (1983). Stockholders and Stakeholder: A New Perspective on Corporate Governance. Californian Management Review, 25 (2), pp. 88-106.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program SPSS Cetakan VII. Semarang: Badan Penerbit Universitas Diponegoro.Gorethai, J. (2019). The Impact of Intellectual Capital Performance on Intellectual Capital DIsclosure in Financial Report (Case Study on Banking Sector Companies Registered on The Indonesia Stock Exchange). Pontianak: University of Tanjungpura.Guthrie, J., & Petty, R. (2000). Intellectual Capital: Australian annual reporting practices. Journal of Intellectual Capital Vol 1, No. 3, pp. 343-352.Guthrie, J., Cuganesan, S., & Wad, L. (2006). Legitimacy Theory: A Story of Reporting Social and Environmental Matters Within the Australian Food and Beverage Industry. Sydney: The University of Sydney.Guthrie, J., Pretty, R., Yongvanic, K., & RIcceri, F. (2004). Using Content Analysis as a Research Method to Inquire to Intellectual Capital Reporting. Journal of Intellectual Capital, 5 (2), pp. 282-293.Haniffa, R., & Cooke, T. E. (2005). The Impact of Culture and Governance on Corporate Social Reporting. Journal of Accounting and Public Policy 24, pp. 391-430.Hernita, S. (2012). Pengaruh Pengungkapan Modal Intelektual Terhadap Biaya Ekuitas dan Biaya Utang (Studi Empiris Pada Perusahaan dengan Teknologi Intensif di Indonesia). Depok: Universitas Indonesia.Husin, N., Ahmad, N., & Sapingi, R. (2011). Intellectual Capital: A Focus on Human Capital Reporting Practice of Top Malaysian Listed Companies. The South East Asian Journal of Management, 5 (1), pp. 51-71.Ikatan Akuntansi Indonesia. (2018). Standar Akuntansi Keuangan Per 1 Januari 2018. Jakarta: IAI.Iranmahd, M., Moeinaddin, M., Shahmoradi, N., & Heyrani, F. (2014). The Effect of Intellectual Capital on Cost of Finance and Firm Value. International Journal of Academic Research in Accounting, Finance and Management Sciences Vol 4 No 2, pp. 1-8.Istianingsih. (2011). Faktor-faktor Penentu Pengungkapan Informasi dan Kinerja Modal Intelektual serta Dampaknya terhadap Kemampuan Imbal Hasil Saham dalam Memprediksi Laba Masa Depan Perusahaan. Disertasi Program Pasca Sarjana Ilmu Akuntansi Fakultas Ekonomi Universitas Indonesia.Kementrian Keuangan Republik Indonesia Badan Pengawas Pasar Modal dan Lembaga Keuangan. (n.d.). Keputusan Ketua Badan Pengawas Pasar Modal dan Lembaga Keuangan Nomor: KEP-347/BL/2012.Khoirunnisa, I., & Cahyati, A. D. (2017). Pengaruh Intellectual Capital Disclosure Terhadap Cost of Equity dan Cost of Debt. Jurnal Riset Akuntansi Keuangan Vol. 8 No. 2, pp. 196-220.Larasati, P., & Noita, N. (2015). Pengaruh Pengungkapan Modal Intelektual Terhadap Cost of Equity Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014. Jurnal Ekonomi, Manajemen dan Perbankan Vol 1 No 3, pp. 78-84.Li, J., Pike, R., & Haniffa, R. (2008). Intellectual Capital Disclosure and Corporate Governance Structure in UK firms. Accounting and Business Research, 38 (2) pp. 137-159.Mangena, M., Pike, R., & and Li, J. (2010). Intellectual Capital Disclosure Practices and Effects in the Cost of Equity Capital: UK Evidence. The institute of Chatered Accountants of Scotland.Mangena, M., Pike, R., & Li, J. (2010). Intellectual Capital DIsclosure Practices and Effects in the Cost of Equity Capital: UK Evidence. The Institue of Chartered Accountants of Scotland.Moeheriono. (2012). Pengukuran Kinerja Berbasis Kompetensi. Jakarta: Raja Grafindo Persada.Mokhova, N., Zinecker, M., & MeluzÃn, T. (2018). Internal Factors Influencing the Cost of Equity Capital. Enterpreneurship and Sustainability Issues, Enterpreneurship and Sustainability Center,, 827-845.Omran, M. A., & El-Galfy, A. M. (2014). Theoritical perspectives on corporate disclosure: a critical evaluation and literature survey. Asian Revew of Accounting, Vol. 22, No. 3, pp. 257-286.Orens, R., Aerts, W., & Lybaert, N. (2009). Intellectual capital disclosure, cost of finance and firm value. Management Decision, Vol 43 No 10 pp. 1536-1564.Priyatno, D. (2018). SPSS Panduan Olah Data bagi Mahasiswa/Umum. Yogyakarta: ANDI.Purnomosidhi, B. (2006). Praktik Pengungkapan Modal Intelektual pada Perusahaan Publik di Bursa Efek Jakarta (BEJ). Jurnal Riset Akuntansi Indonesia, 9 (1), pp. 1-20.Puspitasari, A. (2018). The Practice of Disclosing Human Capital in Bank Jawa Barat and Banten: From the Perspective of Political Economy of Accounting. Pontianak: University of Tanjungpura.Septiani, G., & Taqwa, S. (2019). Pengaruh Intellectual Capital Disclosure dan Leverage terhadap Cost of Equity Capital: Studi Empiris Pada Perusahaan Properti dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2017. Jurnal Eksplorasi Akuntansi Vol. 1, No. 3, Seri D, Agustus 2019, 1337-1353.Setiawati, E., & Agustina, L. (2016). Intellectual Capital Disclosure and Its Implications on Cost of Equity Capital with Information Asymmetry as An Intervening Variable (An Empirical Study on Manufacturing Companies Listed in IDX Year 2012-2014). Accounting Analysis Journal, 5 (4) pp. 271-281.Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Suwardjono. (2014). Teori Akuntansi: Perekayasaan Pelaporan Keuangan (3 ed.). Yogyakarta: BPFE.Ulum, I. (2009). Intellectual Capital: Konsep dan Kajian Empiris. Yogyakarta: PT. Graha Ilmu.Ulum, I. (2012). Investigasi Hubungan antara Kinerja Modal Intelektual dan Praktik Pengungkapannya dalam Laporan Tahunan Perusahaan. Jurnal Ekonomi dan Bisnis, 17(1), pp. 36-45.Ulum, I. (2015). Peran Pengungkapan Modal Intelektual dan Profitabilitas dalam Hubunangan antara Kinerja Modal Intelektual dengan Kapitalisasi Pasar. Semarang: Universitas Diponegoro.Ulum, I. (2017). Intellectual Capital: Model Pengukuran, Framework Pengungkapan & Kinerja Organisasi. Malang: Unversitas Muhammadiyah.Ulum, I., Ghozali, I., & Purwanto, A. (2014). Konstruksi Model Pengukuran Kinerja dan Kerangka Kerja Pengungkapan Modal Intelektual. JAMAL (Jurnal Akuntansi Multiparadigma, Vol. 5, No. 3, pp. 380-392.Ulum, I., Tenrisumpala, A., & Wahyuni, E. D. (2016). Intellectual Capital Disclosure: Studi Komparasi antara Universitas di Indonesia dan Malaysia. Akuntabilitas: Jurnal Ilmu Akuntansi Volume 9 (1), pp. 13-26.Undang Undang No. 20 Tahun 2008. (n.d.).Whiting, R. H., & Miller, J. C. (2008). Voluntary disclosure of intellectual capital in New Zealand annual reports the 'hidden value'. Journal of Human Resource Costing Accounting, Vol. 12, No. 1, pp. 26-50.Widarjo, A. (2018). Analisis Regresi dengan SPSS. Yogyakarta: UPP STIM YKPN.Wulandari, & Prastiwi, A. (2014). PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP COST OF EQUITY CAPITAL Studi Empiris pada Perusahaan yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia Tahun 2012. Dipenogoro Journal of Accounting Volume 3, Nomor 4, Halaman 1.Yulistina, M. (2011). Pengaruh Pengungkapan Intellectual Capital Terhadap Cost of Equity Capital. Semarang: Fakultas Ekonomi Universitas Diponegoror.Zhang, M. (2016). Pengertian Budaya Perusahaan Menurut Para Ahli. Retrieved from Retrieved from Sarjanaku.com: http://www.sarjanaku.comÂ